A Luminescent Metal–Organic Framework as a Turn‐On Sensor for DMF Vapor1. Issue 2 (20th November 2012) - Li, Yu; Zhang, Shanshan; Song, Datong
<x xml:space="preserve">Abstract</x> A real turn‐on: A luminescent lanthanide metal–organic framework shows strong and fast turn‐on responses to N, N‐dimethylformamide (DMF) vapor. The selective turn‐on effect is triggered mainly by DMF–ligand interactions, along with the removal of quencher, water, from the metal coordination sphere.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>